From the Golden Sixties to 2010: half a century of deindustrialisation and labour disputes in Brussels - Jean Vandewattyne (Brussels Studies, 2015)
The article covers almost half a century of strikes which took place in industrial companies in Brussels, beginning with the major strike in the winter of 1960‑61 until 2010. The selection of these labour disputes was based either on certain characteristics of the disputes, such as their harshness and symbolic character, or on their emblematic character with respect to the Brussels economic reality of the company concerned. The article focuses in particular on two major periods. The first period corresponds to the end of the post-war economic boom and was marked by some hard, long and offensive strikes regarding working conditions. In particular, they brought to the fore the question of the position of “foreign” workers in work organisations as well as in the world of trade unions. The second period covers the beginning of the 1980s until 2010, and had the economic crisis, unemployment and new managerial policies as a backdrop. The disputes were defensive, with the negotiation of social plans related to restructuring and the shutting down of sites as their main issue. The question of the respect of union rights was also a reason for the disputes.